Strategic Planning: A Framework for Leading a Department - Ben Beitin (Academic Chairpersons Conference Proceedings, 2016)
This session will provide participants with a brief overview of research related to the chair’s leadership role. Strategic planning will be discussed as a means of managing the chair’s responsibilities. Practical suggestions for how to use strategic planning to increase work efficiency will be offered from the perspective of a new chair.
Keywords: Leadership; Planning; Organization; Effectiveness; Goals